What is the coefficient of x 7 in the expansion of ( 1 + x + 2 x 3 ) 1 0 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
( 1 + x + 2 x 3 ) 1 0 = [ ( 1 + x ) + 2 x 3 ] 1 0
You only need to consider these three terms:
(1 + x)^10
(1+x)^9 · 2x^3
(1 + x)^8 · (2x^3)^2
Other terms don't have x^7.
The coefficient of x^7 in (1 + x)^10 is 10C0 · 10C7 = 120
The coefficient of x^7 in (1+x)^9 · 2x^3 is 10C1 · 9C4 · 2 = 2520
The coefficient of x^7 in (1 + x)^8 · (2x^3)^2 is 10C2 · 8C1 · 2^2 = 1440
120 + 2520 + 1440 = 4080
1 + 1 0 x + 4 5 x 2 + 1 4 0 x 3 + 3 9 0 x 4 + 9 7 2 x 5 + 2 0 7 0 x 6 + 4 0 8 0 x 7 + 7 6 0 5 x 8 + 1 2 7 3 0 x 9 + 2 0 0 4 1 x 1 0 + 3 0 4 2 0 x 1 1 + 4 2 0 2 0 x 1 2 + 5 5 2 0 0 x 1 3 + 7 0 7 4 0 x 1 4 + 8 1 9 8 4 x 1 5 + 9 1 6 8 0 x 1 6 + 1 0 0 8 0 0 x 1 7 + 9 7 4 4 0 x 1 8 + 9 4 0 8 0 x 1 9 + 8 8 7 0 4 x 2 0 + 6 9 1 2 0 x 2 1 + 5 9 5 2 0 x 2 2 + 4 6 0 8 0 x 2 3 + 2 6 8 8 0 x 2 4 + 2 3 0 4 0 x 2 5 + 1 1 5 2 0 x 2 6 + 5 1 2 0 x 2 7 + 5 1 2 0 x 2 8 + 1 0 2 4 x 3 0
Add {} around your exponents (10 or greater) in the LaTeX form, so the sentence won't look so funny anymore.
Problem Loading...
Note Loading...
Set Loading...
Solution for those who don't know Multinomial Theorem,
( 1 + x + 2 x 3 ) 1 0 = r = 0 ∑ 1 0 ( 1 0 r ) ( x + 2 x 3 ) r m i n m p o w e r o f x i n ( x + 2 x 3 ) r = r m a x m p o w e r o f x i n ( x + 2 x 3 ) r = 3 r , s o r ≤ 7 ≤ 3 r ⇒ 2 < r ≤ 7 p a s s i b l e r a r e 3 , 4 , 5 , 6 , 7 & ( x + 2 x 3 ) r = x r ( 1 + 2 x 2 ) r = x r n = 0 ∑ r ( r n ) 2 n x 2 n 2 n + r = 7 s o r o n l y o d d s o n o w o n l y p a s s i b l e ( r , n ) a r e ( 3 , 2 ) , ( 5 , 1 ) , ( 7 , 0 ) ∴ c o f f . o f x 7 i n ( 1 + x + 2 x 3 ) 1 0 = c o f f . o f x 7 i n { ( 1 0 3 ) ( x + 2 x 3 ) 3 + ( 1 0 5 ) ( x + 2 x 3 ) 5 + ( 1 0 7 ) ( x + 2 x 3 ) 7 } = { ( 1 0 3 ) ( 3 2 ) 2 2 + ( 1 0 5 ) ( 5 1 ) 2 1 + ( 1 0 7 ) ( 7 0 ) 2 0 } = 4 0 8 0